Review: Progress in solar cells from hydrogenated amorphous silicon. (September 2017) - Stuckelberger, Michael; Biron, Rémi; Wyrsch, Nicolas; Haug, Franz-Josef; Ballif, Christophe
Abstract: Hydrogenated amorphous silicon ( a -Si:H) has been used for decades—doped and as intrinsic absorber layers—in thin-film silicon solar cells. Whereas their effiency was improved for a long time by the deposition of higher quality absorber layers, recent improvements can be attributed to a better understanding of the interfaces, allowing for their specific engineering. In this review, we briefly resume the state-of-the-art of a -Si:H solar cell technology from growth and characterization of single layers to full solar cells and multijunction devices. Focusing on the absorber layer quality first, we highlight thereafter aspects of interface problematics and discuss the growth and role of doped microcrystalline silicon-oxide layers and approaches of 3D-solar-cell designs in more detail. Although the findings summarized in this review were obtained from thin-film solar cells, we show that a -Si:H is a very versatile material with properties that are of high interest for application in other devices such as heterojunction solar cells, detectors, or optoelectronic devices.